A transparent and defensible process for applicant selection within a Canadian emergency medicine residency program. Issue 2 (March 2020) - Paterson, Quinten S.; Hartmann, Riley; Woods, Rob; Martin, Lynsey J.; Thoma, Brent
ABSTRACT: Objectives: The Canadian Resident Matching Service (CaRMS) selection process has come under scrutiny due to the increasing number of unmatched medical graduates. In response, we outline our residency program's selection process including how we have incorporated best practices and novel techniques. Methods: We selected file reviewers and interviewers to mitigate gender bias and increase diversity. Four residents and two attending physicians rated each file using a standardized, cloud-based file review template to allow simultaneous rating. We interviewed applicants using four standardized stations with two or three interviewers per station. We used heat maps to review rating discrepancies and eliminated rating variance using Z-scores. The number of person-hours that we required to conduct our selection process was quantified and the process outcomes were described statistically and graphically. Results: We received between 75 and 90 CaRMS applications during each application cycle between 2017 and 2019. Our overall process required 320 person-hours annually, excluding attendance at the social events and administrative assistant duties. Our preliminary interview and rank lists were developed using weighted Z-scores and modified through an organized discussion informed by heat mapped data. The difference between the Z-scores of applicants surrounding the interview invitation threshold was 0.18-0.3 standard deviations. Interview performance significantly impacted the final rank list. Conclusions: We describe a rigorous resident selection process for our emergency medicine training program which incorporated simultaneous cloud-based rating, Z-scores, and heat maps. This standardized approach could inform other programs looking to adopt a rigorous selection process while providing applicants guidance and reassurance of a fair assessment.